The Determinants of Healthcare Service Quality in Hospitals in Cities/Districts in Central Java - Adnanti, Wenny Ana; Tri Mulyaningsih (The Es Economics and Entrepreneurship, 2023)
This study aims to analyze the determinants of healthcare service quality in hospitals in cities/districts in Central Java, with healthcare services as the dependent variable and the number of general practitioners, specialist doctors, healthcare personnel, bed capacity, population size, hospital level in cities/districts, and economic growth as the independent variables.The research method used in this study is a descriptive analytic study with a quantitative approach. Secondary data were utilized, including hospital data from the Indonesian Ministry of Health website, economic data from the Central Bureau of Statistics (BPS) of Central Java website, and population data from the Indonesian Ministry of Home Affairs website. The research sample consists of 86 hospitals.The study employs a logistic regression analysis model where the dependent variable is a binary variable. The analysis results indicate a significant positive relationship between the number of specialist doctors and healthcare service quality. However, the number of general practitioners, healthcare personnel, bed capacity, population size, hospital level, and economic growth have less significant influence on healthcare service quality.These findings underscore the importance of human resources factors, such as the number of specialist doctors, in improving healthcare service quality. Therefore, support should be provided to encourage doctors to specialize in various medical fields. It is hoped that these findings can serve as a basis for making better decisions in human resources planning, thereby ensuring the provision of high-quality healthcare services to the public in cities/districts in Central Java.